The effect of composition purple sweet potato flour (Ipomoea batatas L.) and wheat on the physical, chemical and sensory properties in cookies - Rahmalia, Rekha Rizky; Yuliani, Ririn; Yuanda, Afifah Nurfadyah Islami Yuanda; Khoerunnisa, Farah; Sari, Yuli Perwita (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2024)
Cookies are a type of biscuit made from soft dough, high in fat content, relatively crispy when broken, and have a dense cross-sectional texture. The significantly increasing data on wheat flour consumption indicates a very high level of dependence on wheat flour. This is due to the high number of processed food products using wheat flour, necessitating the utilization of flour from local raw materials to explore local potential, one of which is by partially replacing wheat flour with purple sweet potato flour. The aim of this study was to determine the effect of adding purple sweet potato flour on the physical, chemical, and sensory properties of cookies. An experimental method was used with a Completely Randomized Design (CRD) with 3 replications. The formulations used in making cookies with substitution of purple sweet potato flour and wheat flour were (100:0, 90:10, 80:20). Parameters measured included moisture content, protein content, texture, color, and sensory acceptance. The results of data analysis and sensory analysis using Analysis of Variance (ANOVA) showed that the ratio of purple sweet potato flour to wheat flour significantly affected the protein content, color, and texture of cookies. However, it did not significantly affect the moisture content and sensory properties of cookies. The most preferred sample was the 90:10 treatment. Nutritional content: 2.12% moisture content, and 28.10% protein content. Keywords: Cookies, purple sweet potato flour, wheat flour